Method for directly synthesizing NbxTa (2-x) S2C material by catalytic method

The method of directly synthesizing NbxTa2-xS2C materials by using halogen compounds or elemental halogen catalysts at high temperatures solves the problems of complex preparation, high cost and safety hazards in the existing technology, and realizes the preparation of high-performance and low-cost materials, which are suitable for energy storage and catalytic applications.

CN121269711APending Publication Date: 2026-01-06INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511412215.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2026-01-06

AI Technical Summary

Technical Problem

Existing methods for preparing NbxTa2-xS2C materials are complex, costly, and pose safety risks, and their performance is compromised, making them unsuitable for applications such as energy storage and catalysis.

Method used

Using niobium powder, tantalum powder, sulfur powder, and carbon powder as raw materials, and halogen compounds or elemental halogens as catalysts, NbxTa2-xS2C materials are directly synthesized at high temperatures. Through a process flow of ball milling, pressing, sealing, and high-temperature calcination, the intercalation-deintercalation steps are avoided, simplifying the process and reducing energy consumption.

Benefits of technology

A NbxTa2-xS2C material with high energy density and specific surface area has been successfully prepared. It is suitable for lithium battery anodes, with high initial capacity, excellent cycle performance, low cost, and safety and reliability, making it suitable for large-scale commercial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121269711A_ABST
    Figure CN121269711A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of two-dimensional material preparation, and particularly relates to a method for directly synthesizing an Nb < x > Ta < 2-x > S2C material through a catalytic method. According to the method, niobium powder, tantalum powder, sulfur powder and carbon powder are used as raw materials and sealed in an ampoule bottle to isolate air, and a halogen compound or a halogen simple substance is used as a catalyst to directly synthesize NbxTa (2-x) S2C at high temperature. According to the method, Nb < x > Ta < 2-x > S2C is directly synthesized by heating in an ampoule bottle without air, so that the process flow is simplified, the preparation temperature is reduced, the reaction time is shortened, the use of organic solvents such as acetonitrile is avoided, and the material preparation cost is reduced. Therefore, the method belongs to the Nb < x > Ta < 2-x > S2C preparation method which is low in cost, simple in process, safer and more reliable, and can be widely applied to the fields of energy storage batteries, electromagnetic interference shielding, catalysis and plasma metamaterials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-dimensional material preparation technology, specifically relating to a catalytic method for the direct synthesis of Nb. x Ta 2-x The method for S2C materials, which can be widely used in energy storage batteries, electromagnetic interference shielding, catalysis, and plasma metamaterials. Background Technology

[0002] Since the discovery of graphene in 2004 using a "tear-off tape" method, the preparation, properties, and applications of two-dimensional materials have attracted considerable attention. Following graphene, researchers have subsequently discovered a series of novel two-dimensional materials, encompassing compounds with various structures and properties, further expanding the family of two-dimensional materials. Among them, transition metal dichalcogenides and transition metal carbides have garnered widespread attention due to their unique structures, special properties, and rich functionalities. The challenges encountered in the recombination of transition metal carbides and transition metal dichalcogenides in electrochemical energy conversion and storage stem from interface problems caused by the inherent differences in their structures and properties. Therefore, integrating these two material families into a unified system hinges on eliminating interfaces that can lead to complexity and performance barriers. Materials that completely fuse the two materials together are called transition metal carbides. This fused material enables seamless charge transport, thereby improving overall performance. This strategy not only overcomes the limitations of single materials but also optimizes performance through synergistic effects, opening new prospects for electrochemical applications. Furthermore, this material also holds great potential in fields such as superconductivity, triboelectricity, and photothermal conversion. This emerging two-dimensional material is developing rapidly.

[0003] Nb x Ta 2-x S2C materials belong to the category of two-dimensional transition metal carbosulfides. Besides S2C, other synthesized transition metal carbosulfides include Nb2Se2C and Ta2Se2C. Nb x Ta 2-x S2C material exists in a layered state, with carbon atoms in the middle, transition metal atoms on both sides of the carbon atoms, and sulfur atoms as terminal atoms connected to the transition metal atoms. Nb x Ta 2-x In addition to inheriting the excellent properties of traditional two-dimensional materials, S2C materials exhibit properties similar to transition metal dichalcogenides and transition metal carbides, while also possessing high energy density, high volumetric capacitance, and good electromagnetic shielding. These properties are beneficial for many applications, including energy storage, catalysis, electromagnetic interference shielding, sensors, and as plasma metamaterials.

[0004] Currently Nb x Ta 2-xConventional methods for preparing S2C materials involve localized chemical processes, requiring the insertion of Cu or Fe atoms followed by the extraction of the relevant atoms. This process is complex, time-consuming, and costly. The extraction process requires the use of iodine-acetonitrile solutions, posing safety concerns and potentially affecting the material's structure and properties. Furthermore, the extraction process disrupts the material's layered structure, leading to a decrease in specific surface area and impaired energy storage performance.

[0005] Patent publication number CN119081751A proposes a new type of solid lubricant (Nb). x Ta 1-x The preparation method of 2CSe2, although involving Nb-Ta-C system materials, has Se in the raw materials and the powder product is a selenide. The selenide has low chemical stability and energy storage performance (such as lithium battery anode capacity). The product is mainly used in the lubrication field and cannot meet the requirements of target scenarios such as energy storage and catalysis. In terms of process, it is necessary to coat the surface of the reactant discs with a KCl-NaCl salt shell, and then wash and desalt it. The reaction depends on polytetrafluoroethylene and high-temperature heat treatment. Patent CN1346699A proposes a halogen-promoted polymetallic oxide catalyst for the gas-phase oxidation of alkanes to prepare unsaturated carboxylic acids or the oxidation of ammonia to prepare unsaturated nitriles. The raw materials are mainly Mo, W, V, Te, etc., and halogens (Br, Cl, etc.) are only used as catalyst activity promoters to improve the selectivity of the oxidation reaction, not for catalyzing the direct synthesis of specific layered materials from the raw materials.

[0006] Therefore, it is necessary to develop a direct, safe, efficient, and low-cost method for synthesizing Nb. x Ta 2-x The preparation method of S2C material has become the key to promoting the industrialization of this material. Summary of the Invention

[0007] The purpose of this invention is to provide a catalytic method for the direct synthesis of Nb. x Ta 2-x A method for S2C materials, which enables efficient, inexpensive, and safe direct synthesis of Nb. x Ta 2-x S2C materials avoid the use of organic solvents such as acetonitrile, simplifying the process and shortening the reaction time, thus solving the problems of existing Nb. x Ta 2-x The preparation of S2C involves complex intercalation-deintercalation processes, safety risks associated with organic solvents, damage to material properties, and high costs.

[0008] The technical solution adopted in this invention is as follows:

[0009] A catalytic method for the direct synthesis of Nb x Ta 2-xThe S2C material method uses niobium powder, tantalum powder, sulfur powder, and carbon powder as raw materials, sealed in ampoules to isolate them from air, and uses halogen compounds or elemental halogens as catalysts to directly synthesize the material at high temperatures. The chemical formula of the material is Nb. x Ta 2-x S2C, x = 0 to 2.

[0010] The catalytic method for direct synthesis of Nb x Ta 2-x The preferred method for S2C materials is Nb. x Ta 2-x In S2C, x = 0.5 to 1.5.

[0011] The catalytic method for direct synthesis of Nb x Ta 2-x The method for S2C materials includes the following steps:

[0012] 1) Raw material mixing: Niobium powder, tantalum powder, sulfur powder and carbon powder are mixed and placed in a ball mill jar, ethanol is added, ball milling is performed and then dried. After drying, halogen compounds or halogen elemental powders are added and mixed evenly.

[0013] 2) Pressing and sealing: Press the mixture obtained in step 1) into pellets or discs, place the pellets or discs in a graphite crucible, place the graphite crucible in an ampoule, remove the air, and then seal it.

[0014] 3) High-temperature calcination: The ampoules obtained in step 2) are calcined at high temperature and then cooled to room temperature;

[0015] 4) Product collection: Open the ampoule obtained in step 3) and collect the Nb from the crucible. x Ta 2-x S2C material removed.

[0016] The catalytic method for direct synthesis of Nb x Ta 2-x In the method for S2C materials, in step 1), the molar ratio of niobium powder, tantalum powder, sulfur powder, carbon powder, halogen compound or halogen element powder is x:2-x:2:1:(0.00001~0.002).

[0017] The catalytic method for direct synthesis of Nb x Ta 2-x In the method for S2C material, step 1) involves a total mass of raw material and a volume ratio of anhydrous ethanol of 1 g: 2-3 mL, a ball milling speed of 150-160 rpm, a ball milling time of 2-4 h, a drying temperature of 60-70 °C, and a drying time of 6-8 h.

[0018] The catalytic method for direct synthesis of Nb x Ta 2-xIn the method for S2C materials, step 1) uses niobium powder with a particle size of 10-30 μm, tantalum powder with a particle size of 10-30 μm, sulfur powder with a particle size of 100-300 mesh, carbon powder with a particle size of 100-400 mesh, and halogen compounds or halogen elements with a particle size of 5-10 μm.

[0019] The catalytic method for direct synthesis of Nb x Ta 2-x In the S2C material method, step 2) involves compressing the pellets at a pressure of 15–20 MPa, using pellets or discs with a diameter of 12–14 mm and a thickness of 2–3 mm, and removing air from the ampoules until the pressure is ≤10 MPa. -3 After Pa, seal.

[0020] The catalytic method for direct synthesis of Nb x Ta 2-x In the method for S2C materials, step 3) involves calcining at a heating rate of 5℃ / min to 1100-1400℃, with a holding time of 5-72h.

[0021] The catalytic method for direct synthesis of Nb x Ta 2-x The S2C material method uses hexachlorobenzene, hexabromobenzene, niobium chloride, or tantalum bromide as the halogen compound and iodine as the halogen element.

[0022] The design concept of this invention is:

[0023] Conventional localized chemical methods require the insertion and extraction of Cu / Fe atoms, which is cumbersome, time-consuming, and costly. The extraction process uses an acetonitrile solution of iodine, posing a safety risk due to organic solvent volatilization and potentially damaging the layered structure of the material, thus reducing its energy storage performance. This invention provides a raw material system precisely matched to Nb. x Ta 2-x The S2C layered structure (Nb powder and Ta powder provide transition metal sites, S powder is the terminal sulfur source, and C powder is the intermediate carbon source, forming a layered stacked structure of sulfur-transition metal-carbon-transition metal-sulfur) introduces halogen compounds (such as hexabromobenzene) or halogen elements as catalysts, utilizing halogen atoms to lower the activation energy of the reaction between raw materials, achieving direct synthesis without intercalation-deintercalation. The process design includes ball milling mixing, pressing and sealing, and high-temperature calcination. Ball milling ensures uniform dispersion of raw materials, and the ampoules are vacuum-sealed to isolate air and prevent oxidation. Calcination is carried out at a uniform heating rate of 5℃ / min to 1100-1400℃ and held for 5-72 hours, ensuring complete crystal growth while avoiding local overheating that could damage the structure. Furthermore, this invention's Nb... x Ta 2-xIn the preparation of S2C materials, the molar ratio of raw materials such as niobium powder, tantalum powder, sulfur powder, carbon powder, halogen compound or halogen element powder is x:2-x:2:1:(0.00001~0.002). The design basis for the catalyst dosage of 0.00001~0.002 molar ratio is that too much catalyst will tend to generate transition metal carbides, while too little catalyst will prevent the synthesis of the target product.

[0024] The advantages and beneficial effects of this invention are as follows:

[0025] 1. This invention successfully prepared Nb x Ta 2-x S2C materials are small in size with a specific surface area of ​​3–50 μm, exhibiting excellent energy storage performance. When used as lithium battery anodes, Nb2S2C and Ta2S2C materials can achieve initial capacities of 399 mAh / g and 362 mAh / g, respectively, which are superior to existing transition metal carbides and disulfides.

[0026] 2. The present invention Nb x Ta 2-x The S2C material preparation method is simple, eliminating the insertion-deintercalation step and shortening the process. It does not require the use of iodine acetonitrile solution or other methods for treatment. The calcination temperature of 1100-1400℃ is lower than that of the traditional local chemical method, resulting in significantly reduced energy consumption, relatively low cost, and greater safety and reliability. It has value for large-scale commercial use.

[0027] 3. Nb prepared by this invention x Ta 2-x S2C material has a high energy density of 0.1Ag. -1 At current density, the charging specific capacity reaches 399mAhg. -1 Its specific surface area can reach 3 to 50 μm. Attached Figure Description

[0028] Figure 1 The image shows a scanning electron microscope (SEM) image of the Nb2S2C material prepared in Example 1.

[0029] Figure 2 The image shows a SEM image of the Ta2S2C material prepared in Example 2.

[0030] Figure 3 The image shows a SEM image of the NbTaS2C material prepared in Example 3. Detailed Implementation

[0031] The present invention will now be further described in detail with reference to embodiments and accompanying drawings.

[0032] Example 1

[0033] In this embodiment, the raw material powders used are niobium powder with a particle size of 10-30 μm, sulfur powder with a particle size of 100-300 mesh, carbon powder with a particle size of 100-400 mesh, and hexabromobenzene powder with a particle size of 5-10 μm. The method for directly synthesizing Nb2S2C material based on halogen compound catalysis is as follows:

[0034] 1) Mix 14.18g niobium powder, 4.90g sulfur powder and 0.92g carbon powder in a ball mill jar, add 8mL anhydrous ethanol, and ball mill at 152rpm for 2h. Then place it in a forced-air drying oven and dry at 70℃ for 8h. After drying, add 0.002g hexabromobenzene powder and mix well.

[0035] 2) Take 3g of the mixture obtained in step 1) and press it into a disc with a diameter of 14mm under a pressure of 15MPa. Place the disc into a graphite crucible, then place the crucible into an ampoule. Use a molecular pump to evacuate the air from the ampoule until the pressure is 1×10⁻⁶. -4 After sealing (Pa);

[0036] 3) Place the ampoule obtained in step 2) into an electric furnace, heat it to 1250°C at a heating rate of 5°C / min, keep it at that temperature for 24 hours, and then cool it to room temperature.

[0037] 4) Break the ampoule that has been cooled to room temperature in step 3), remove the black powder from the graphite crucible, and obtain Nb2S2C material.

[0038] like Figure 1 As shown, the sample exhibits a lamellar structure with a cross-shaped distribution between the lamellars and a grain size of 100–500 nm, which is consistent with the morphological characteristics of Nb₂S₂C material.

[0039] In this embodiment, the performance indicators of the Nb2S2C material are as follows: specific surface area can reach 3-50 μm, and it has excellent electrochemical performance at 0.1 Ag. -1 At current density, the charging specific capacity reaches 362mAhg. -1 .

[0040] Example 2

[0041] In this embodiment, the raw material powders used are tantalum powder with a particle size of 10-30 μm, sulfur powder with a particle size of 100-300 mesh, carbon powder with a particle size of 100-400 mesh, and hexabromobenzene powder with a particle size of 5-10 μm. The method for directly synthesizing Ta2S2C material based on halogen compound catalysis is as follows:

[0042] 1) Mix 16.52g tantalum powder, 2.92g sulfur powder and 0.548g carbon powder in a ball mill jar, add 6mL anhydrous ethanol, and ball mill at 152rpm for 2h. Then place it in a forced-air drying oven and dry at 70℃ for 8h. After drying, add 0.002g hexabromobenzene powder and mix well.

[0043] 2) Take 3g of the mixture obtained in step 1) and press it into a disc with a diameter of 14mm under a pressure of 15MPa. Place the disc into a graphite crucible, then place the crucible into an ampoule. Use a molecular pump to evacuate the air from the ampoule until the pressure is 1×10⁻⁶. -4 After sealing (Pa);

[0044] 3) Place the ampoule obtained in step 2) into an electric furnace, heat it to 1300℃ at a heating rate of 5℃ / min, keep it at that temperature for 24 hours, and then cool it to room temperature.

[0045] 4) Break the ampoule that has been cooled to room temperature in step 3), remove the black powder from the graphite crucible, and obtain the Ta2S2C material.

[0046] like Figure 2 As shown, the sample exhibits a lamellar structure with parallel stacking between the lamellars and clear boundaries between them. The grain size ranges from 100 to 500 nm, which is characteristic of the morphology of Ta2S2C material.

[0047] In this embodiment, the performance indicators of the Ta2S2C material are as follows: specific surface area can reach 3-50 μm, and at 0.1 Ag... -1 At current density, the charging specific capacity reaches 399mAh g. -1 .

[0048] Example 3

[0049] In this embodiment, the raw material powders used are tantalum powder with a particle size of 10-30 μm, niobium powder with a particle size of 10-30 μm, sulfur powder with a particle size of 100-300 mesh, carbon powder with a particle size of 100-400 mesh, and hexabromobenzene powder with a particle size of 5-10 μm. The method for directly synthesizing NbTaS2C material based on halogen compound catalysis is as follows:

[0050] 1) Mix 7.09g niobium powder, 13.96g tantalum powder, 4.93g sulfur powder and 0.92g carbon powder and put them into a ball mill jar. Add 8mL of anhydrous ethanol and ball mill at 152rpm for 2h. Then put it into a forced-air drying oven and dry at 70℃ for 8h. After drying, add 0.002g hexabromobenzene powder and mix well.

[0051] 2) Take 3g of the mixture obtained in step 1) and press it into a disc with a diameter of 14mm under a pressure of 15MPa. Place the disc into a graphite crucible, then place the crucible into an ampoule. Use a molecular pump to evacuate the air from the ampoule until the pressure is 1×10⁻⁶. -4 After sealing (Pa);

[0052] 3) Place the ampoule obtained in step 2) into an electric furnace, heat it to 1250°C at a heating rate of 5°C / min, keep it at that temperature for 24 hours, and then cool it to room temperature.

[0053] 4) Break the ampoule from step 3) after it has cooled to room temperature, remove the black powder from the graphite crucible, and obtain...

[0054] NbTaS2C material.

[0055] like Figure 3 As shown, the sample has a lamellar structure with some layers arranged in a cross-shaped pattern. The grain size is 100–500 nm, which is consistent with the morphological characteristics of NbTaS2C material.

[0056] In this embodiment, the performance indicators of the NbTaS2C material are as follows: specific surface area can reach 3-50 μm, and at 0.1 Ag... -1 At current density, the charging specific capacity reaches 388mAh g. -1 .

[0057] The results of this invention demonstrate that the method uses halogen compounds or elemental halogens as catalysts to directly synthesize Nb by heating in an air-evacuated ampoule. x Ta 2-x S2C simplifies the process, lowers the preparation temperature, shortens the reaction time, avoids the use of organic solvents such as acetonitrile, and reduces the cost of material preparation. It can be used to prepare Nb. x Ta 2-x When S2C is used as the negative electrode in lithium batteries, the initial capacity of Nb2S2C is ≥362mAh / g, and the initial capacity of Ta2S2C is ≥399mAh / g, with a capacity retention rate of ≥85% after 50 cycles. Therefore, this method is a low-cost, simple, and safer / more reliable Nb2S2C method. x Ta 2-x S2C preparation method.

Claims

1. A process for the direct synthesis of Nb x Ta 2-x A process for the direct synthesis of S2C material, characterized in that, The Nb powder, Ta powder, S powder and C powder are used as raw materials, sealed in ampoule bottles to isolate air, and a halogen compound or halogen element is used as a catalyst to directly synthesize a material with a chemical formula of Nb x Ta 2-x S2C, x = 0-2.

2. A process for the direct synthesis of Nb x Ta 2-x A process for the direct synthesis of Nb Preferably, Nb x Ta 2-x x in S2C = 0.5-1.

5.

3. A process for the direct synthesis of Nb x Ta 2-x A process for the production of S2C material, characterized by The method comprises the following steps: 1) mixing raw materials: put niobium powder, tantalum powder, sulfur powder and carbon powder into a ball mill tank, add ethanol, dry after ball milling, and then add halogen compound or halogen element powder and mix; 2) pressing and sealing: press the mixture obtained in step 1) into a ball or a round sheet, put the ball or the round sheet into a graphite crucible, then put the graphite crucible into an ampoule, and seal the ampoule after removing the air therein; 3) high-temperature calcination: cool the ampoule obtained in step 2) to room temperature after high-temperature calcination. 4) Product collection: The ampoule from step 3) is opened and the Nb x Ta 2-x S2C material is removed.

4. A catalytic direct synthesis of Nb x Ta 2-x A method of S2C material, characterized by, In step 1), the molar ratio of niobium powder, tantalum powder, sulfur powder, carbon powder, halogen compound or halogen element powder is x:2-x:2:1:(0.00001-0.002).

5. A catalytic direct synthesis of Nb x Ta 2-x A method of S2C material, characterized by, In step 1), the volume ratio of the total mass of raw materials to anhydrous ethanol is 1g:2-3mL, the ball milling speed is 150-160rpm, the ball milling time is 2-4h, the drying temperature is 60-70℃, and the drying time is 6-8h.

6. A catalytic direct synthesis of Nb x Ta 2-x A method of S2C material, characterized by, In step 1), the particle size of niobium powder is 10-30μm, the particle size of tantalum powder is 10-30μm, the particle size of sulfur powder is 100-300 mesh, the particle size of carbon powder is 100-400 mesh, and the particle size of halogen compound or halogen element is 5-10μm.

7. A catalytic direct synthesis of Nb x Ta 2-x A method of S2C material, characterized by, In step 2), the briquetting pressure is 15-20 MPa, the diameter of the briquette or disc is 12-14 mm, the thickness is 2-3 mm, and the air in the ampoule is extracted to a pressure of ≤10 Pa before sealing. -3 Pa before sealing.

8. A catalytic direct synthesis of Nb x Ta 2-x A method of S2C material, characterized by, In step 3), the calcination is carried out at a temperature rising rate of 5℃ / min to 1100-1400℃, and the holding time is 5-72h.

9. A catalytic direct synthesis of Nb according to claim 3 x Ta 2-x A method of S2C material, characterized by, The halogen compound is hexachlorobenzene, hexabromobenzene, niobium chloride or tantalum bromide, and the halogen element is iodine.

Citation Information

Patent Citations

  • Preparation method of novel solid lubricant (NbxTa1-x) 2CSe2

    CN119081751A

  • Halogen promoted polymetallic oxide catalyst

    CN1346699A